THE EFFORTS OF MARITAL RECONCILIATION IN REDUCING DIVORCE RATES - Hasnidar,; Supardin,; Marilang, (International Journal of Islamic Studies, 2022)
This study discusses the arguing family members are involved in the application of the concepts and procedures of engaging a third party or intermediary. This research is a research library. Based on the research findings that have been discussed, husband-wife disputes and mediators can prevent divorce, and can apply and implement the following principles and mechanisms in the process of reconciliation efforts: fairness, realistic and evidence-based, systematic, tactical, strategic, and courageous; the decision through a non-litigation process to appoint family or community leaders; the decision through a semi-litigation process by presenting the parties and concluding with a written assessment by conciliation or expert judgment, so that it might affect how effective it is at reducing the divorce rate, including effective, less effective, and ineffective.